Weight change during long-term treatment with lurasidone. (November 2015) - Meyer, Jonathan M.; Mao, Yongcai; Pikalov, Andrei; Cucchiaro, Josephine; Loebel, Antony
<x xml:space="preserve">Abstract</x> The objective of this analysis was to evaluate the effect of 12 months of treatment with lurasidone on weight in patients with schizophrenia. Post-hoc, observed-case analysis included pooled data from six studies on 40–160 mg/day lurasidone; two studies included active comparators (2–6 mg/day risperidone or 200–800 mg/day quetiapine XR). Overall, 593 patients completed 12 months of treatment (N=471 lurasidone, N=89 risperidone, N=33 quetiapine XR). The mean baseline weight was 72.8, 80.8, and 72.4 kg in the lurasidone, risperidone, and quetiapine XR groups, respectively. The mean weight change at month 12 was −0.4 kg with lurasidone, +2.6 kg with risperidone, and +1.2 kg with quetiapine XR. Weight gain of at least 7% from study baseline was observed in 16.0, 25.8, and 15.2% of patients, and weight loss of at least 7% was seen in 18.5, 6.7, and 9.1% of patients treated with lurasidone, risperidone, and quetiapine XR, respectively. A shift from normal/underweight baseline BMI status to overweight/obese at month 12 occurred in 10.2, 27.6, and 15.0% of patients in the lurasidone, risperidone, and quetiapine XR groups, respectively. Conversely, 14.3, 1.7, and 7.7% of patients, respectively, shifted from overweight/obese to normal/underweight. In summary, a low potential for clinically significant weight gain was observed in patients with schizophrenia treated continuously with lurasidone for 12 months.